2014
DOI: 10.1177/000313481408000820
|View full text |Cite
|
Sign up to set email alerts
|

One Decade of Experience with Endoscopic Stenting for Intrathoracic Anastomotic Leakage after Esophagectomy: Brilliant Breakthrough or Flash in the Pan?

Abstract: Management of intrathoracic anastomotic leakage after esophagectomy by means of endoscopic stent insertion has gained wide acceptance as an alternative to surgical reintervention. Between January 2004 and March 2013 all patients who underwent esophagectomy at a German high-volume center for esophageal surgery were included in this retrospective study. The study comprises 356 patients. Anastomotic leakage occurred in 49 cases. There were no significant differences in age, American Society of Anesthesiologists (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 39 publications
0
19
0
Order By: Relevance
“…In addition, serious complications related to SEMS have also been reported (9,10,12). Schweigert et al (13,14) reported that 29 patients underwent SEMS after being diagnosed with anastomotic leakage, and the results showed a high incidence of stent-related complications. Among the 29 patients, 3 (10.3%) had aortic erosion, 1 (3.4%) had intestinal bleeding due to stent displacement, and 1 (3.4%) had airway obstruction.…”
Section: Discussionmentioning
confidence: 98%
“…In addition, serious complications related to SEMS have also been reported (9,10,12). Schweigert et al (13,14) reported that 29 patients underwent SEMS after being diagnosed with anastomotic leakage, and the results showed a high incidence of stent-related complications. Among the 29 patients, 3 (10.3%) had aortic erosion, 1 (3.4%) had intestinal bleeding due to stent displacement, and 1 (3.4%) had airway obstruction.…”
Section: Discussionmentioning
confidence: 98%
“…Mortality rates of anastomotic leaks have been reported as high as 25-45%. [10][11][12][13] Our approach to the management of postoperative leak has evolved since we began performing MIE in 1998. Conventional management consisted of reoperative thoracotomy with possible gastrointestinal diversion, which is an invasive life-saving operation that requires gastrointestinal reconstruction at a later date.…”
Section: Discussionmentioning
confidence: 99%
“…Anastomotic Leakage (AL) is still a feared and life-threatening complication after Ivor Lewis Esophagectomy (ILE) with reported incidence rates of 5-25% and mortality rates up to 20-40 [1][2][3][4][5]. The classification of the Esophagectomy Complications Consensus Group (ECCG) has been introduced to differentiate between different types of AL [6].…”
Section: Introductionmentioning
confidence: 99%